TECHNOLOGICAL IMPLICATIONS IN EDUCATIONAL CONTEXTS FROM THE THEORETICAL ASSUMPTIONS OF THE PEDAGOGY OF AFFECTION - Javier A. Bautista C.; Marlon E. Contreras J. (LÍNEA IMAGINARIA, 2025)
The technological implications in educational contexts arise from the avalanche that is lived in society today with cutting-edge instructional resources or otherwise what is handled in terms of artificial intelligence; every day new teaching options appear that go in terms of virtual education, augmented reality or otherwise everything that enclose the platforms and repositories that are essential source in the teaching processes and this is how the present general objective arises: To reflect on the technological implications in educational contexts from the theoretical assumptions of the pedagogy of affection with an approach to Colombian basic education. The methodology used was framed in a qualitative research focused on documentary analysis; which brought as a result that the technological implications in education is a trend that must be assumed from the classroom and where it is pertinent to involve the pedagogy of affection that will undoubtedly humanize the use of technologies in education; from there emerges a great conclusion that indicates that teachers within their pedagogical action should establish the basis for an adequate use of technologies more human impregnated with the pedagogy of affection in order to generate a teaching model focused on the quality of educational processes.